Investigating the Relationship Between Financial Integration and Economic Growth in the East African Community - Nzioka, Onesmus Mutunga (European Scientific Journal, ESJ, 2017)
This study set out to investigate the relationship between financial integration and economic growth in the EAC community states. Secondary data on financial integration and GDP was obtained from worldbank and the East African Community(EAC) community secretariat. The data was subjected to simple linear regression and correlation analysis to achieve the set objective. The study found that, Gross capital flow to GDP (financial openness) is positively correlated to economic growth (r=0.2093, p <0.05). The study also found that, 3.98% of the variations in economic growth, as measured by GDP per capita, within the countries are explained by financial integration, as measured by the ratio of gross capital flows, 38.98% of the variations in economic growth between the countries are explained by financial integration while 4.38% of the variations in economic growth of the East African communityEAC as an economic bloc (considering panel data) are explained by financial integration. The findings confirm that, when capital flows increase, economic growth also increases, pointing to the necessity of the East African member states to explore ways of increasing the capital flows between the countries. The researcher recommends conducting of a comparative study between the old and the new EAC to establish whether the inclusion of Rwanda and Burundi, has had any positive impact (catalyzed) on the level of financial integration and economic growth.